Implementing supply chain information integration in China: The role of institutional forces and trust⋆ - Cai, Shaohan; Jun, Minjoon; Yang, Zhilin (Journal of Operations Management, 2010)
AbstractThis study investigates the effects of Chinese companies’ institutional environment on the development of trust and information integration between buyers and suppliers. Three aspects of China's institutional environment are salient: legal protection, government support, and the importance of guanxi (interpersonal relationships). This study uses structural equation modeling to analyze data collected from 398 Chinese manufacturing companies. Government support and importance of guanxi significantly affect trust, which subsequently influences two elements of information integration, namely, information sharing and collaborative planning. Furthermore, the importance of guanxi has a direct, positive impact on information sharing, and government support has a direct, positive effect on both information sharing and collaborative planning.